Hip abductor strength and fatigue are associated with activity levels more than 1 year after total hip replacement. Issue 5 (28th November 2017) - Foucher, Kharma C.; Cinnamon, Christopher C.; Ryan, Colleen A.; Chmell, Samuel J.; Dapiton, Kris
ABSTRACT: Despite improvements in pain and function, people who undergo total hip arthroplasty (THR) may not always return to desired levels of physical activity (PA). The factors associated with low activity levels are not fully understood. Abductor weakness and fatigue have both been proposed as factors that limit activity in older adults or people with hip osteoarthritis, but have not been investigated after THR. We hypothesized that abductor weakness and fatigue are associated with lower activity levels in people who have undergone a THR and that fatigue mediates the association between abductor strength and activity. We evaluated 16 subjects (24 ± 10 months post‐THR; age 56.8 ± 8.4 yrs; BMI 31 ± 7 kg/m 2 ). Fatigue was assessed using the PROMIS fatigue short‐form 7a. Peak isometric hip abductor torque was assessed using a dynamometer with subjects in a sidelying position. We assessed activity level using the UCLA activity score. We used Pearson correlations to explore the associations among the variables. Next we used a three‐step linear regression procedure to test whether or not fatigue acted as a mediator between abductor torque and UCLA activity scores. Higher abductor torque was associated with less fatigue ( R 2  = 0.275; p  = 0.037) and with higher UCLA scores ( R 2  = 0.488, p  = 0.003). Higher fatigue was associated with lower UCLA scores ( R 2  = 0. 307, p  = 0.017), however there was no evidence of mediation. This suggests that addressing both abductor strength and fatigue may increase physical activity. Statement of Clinical Significance : Fatigue and abductor weakness should be evaluated in sedentary THR patients presenting for long‐term follow‐up. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1519–1525, 2018.